Extended Motor Evoked Potentials Monitoring Helps Prevent Delayed Paraplegia After Aortic Surgery. Issue 4 (8th March 2016) - See, Reiner B.; Awosika, Oluwole O.; Cambria, Richard P.; Conrad, Mark F.; Lancaster, Robert T.; Patel, Virendra I.; Chitilian, Hovig V.; Kumar, Sandeep; Simon, Mirela V.
Abstract : Objective: Motor evoked potentials (MEPs) monitoring can promptly detect spinal cord ischemia (SCI) from aortic clamping during open thoracoabdominal aneurysm repair (OTAAR) with distal aortic perfusion (DAP) and thus help decrease the risk of immediate postoperative SCI (IP‐SCI). However, neither stable MEPs during aortic clamp interval (ACI) nor absence of IP‐SCI eliminate the possibility of delayed postoperative SCI (DP‐SCI). We hypothesized that extension of MEPs monitoring beyond ACI can also help decrease the risk of DP‐SCI. Methods: We identified 150 consecutive patients at our institution between April 2005 and October 2014 who underwent OTAAR with DAP and MEPs monitoring and had no IP‐SCI. Using logistic regression analysis, we studied the independent effect of extended MEPs monitoring on the risk of developing DP‐SCI. We used a propensity score analysis to adjust for potential confounders, such as poorly controlled hypertension, previous aneurysm surgery, splenectomy, acute aortic dissection, aneurysm type, older age, and history of diabetes and smoking. Results: From the 150 patients, 129 (86%) remained neurologically intact whereas 21 (14%) developed DP‐SCI. Nineteen of these twenty‐one patients (90%) had no extended monitoring. Fifty‐seven of fifty‐nine (97%) patients who benefited from extended monitoring had no DP‐SCI ( p = 0.003). Extended MEPs monitoring was independently associated with decreased risk of DP‐SCI (odds ratio = 0.14; 95% confidence interval: 0.03, 0.65; p = 0.01). Interpretation: MEPs detect the lowest systemic blood pressure that ensures appropriate spinal cord perfusion in the postoperative period. Thus, they inform the hemodynamic management of patients post‐OTAAR, particularly in the absence of a reliable neurological exam. Ann Neurol 2016;79:636–645